The formula for a social Europe: Complementary social policy plus a monetary union and internal market compatible with the European Social Model - Daniel Seikel (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2021)
[Conclusion] The strengthening of the social dimension of the EU is back on the agenda of European politics. The European Pillar of Social Rights, the revision of the Posted Workers Directive (Directive 96/71/EC), and the initiative for a Euro-pean minimum wage are interpreted by some as a turning point. However, the European Pillar of Social Rights is not legally binding, the revision of the Posted Workers Directive (Directive 96/71/EC) basically only repairs the damage caused by the CJEU's jurisprudence, and the future of the European minimum wage is completely open. The road to a more social Europe is still very long. Against this background, this Policy Brief asks how a formula for a social Europe could look like. Based on the assessment that European social policy is limited by structural bound-aries, I present a concept that takes these limitations into account. The for-mula for strengthening the social dimension of the EU can be formulated as follows: social minimum standards plus a reconfiguration of the internal mar-ket and EMU in a way that is compatible with the pillars of the European Social Model. The goal of the programme is the strengthening of the Euro-pean Social Model which is based on national institutions that have evolved over time and that are to be protected and developed further. All of the proposed measures would of course have to clear the high hurdles of the European decision-making processes which I discussed in the second section. Thus, progressive Europeans will still have to fight long and hard for a more social Europe. Without doubt, a common vision of a social Europe agreed to by all would be helpful. This Policy Brief is meant as a contribution to such a discussion.
Keywords: 330